Caractériser la notion de médiation en didactique des langues à l’ère du numérique : apports d’une réflexion plurielle en ingénierie(s) - Cédric Brudermann; Jose Aguilar; Grégory Miras; Dagmar Abendroth-Timmer; Ramona Schneider; Lin XUE (Recherches en didactique des langues et des cultures)
In this paper, we propose a threefold reflection on the notion of mediation in the digital age. To do so, we first present a state-of-the-art review of the notion to explore how the recent literature of the field (applied linguistics and educational sciences) perceives this notion. Then, the notion of mediation is studied from an instructional design viewpoint. To do so, particular emphasis is given to a Franco-German blended learning course dedicated to pre service language teachers (n = 54). Eventually, those pre service language teachers’ beliefs about the concept of mediation are analyzed. Cross-references and comparison of the data led to a first version of a model whose aim is to stimulate reflection on the notion of mediation in the digital era.